Atlantic Resort & Spa - Santos, Nathielen Rambo dos (2022)
The Atlantic Resort & Spa is a four star hotel located on the beach in Palhoça - SC. Cujo, aims to provide users with the best accommodation and leisure, connecting with nature and contemplating the beauties of Santa Catarina. The same, has citizens of the municipality and tourists of all ages as users, since the program includes activities for living, leisure, fun, and entertainment for all audiences. The creation of the resort is intended to develop the local economy, as tourism is one of the fastest growing sectors internationally, being responsible, according to the world tourism organization, for 10% of the world's GDP and one in every eleven jobs in the country. world, therefore, the project seeks to improve the quality of life in the region, providing jobs and well-being to the population. The project aims, as a priority, the integration and preservation of nature, proposing to minimize the ecological footprint. With that in mind, all environments are designed prioritizing views while maintaining direct contact with nature, including outdoor activities, living spaces and leisure. The project was created based on the intention of improving and enhancing man's relationships with nature. Its needs program includes accommodation, events center, administration, departures and arrivals, coworking rooms, roof garden, and leisure and entertainment spaces, such as outdoor and indoor heated pools, with DJ and wet bar being everything -include rest areas, massage, pilates, gym, cinema and several games rooms, as well as restaurants and food spaces scattered around for better service.